(untitled) (Economic and Political Thought, 2023)
European Parliament elections are the second largest democratic elections in the world held in the European Union member states. By voting in these elections, EU citizens have a direct impact on the composition of the European Parliament and its decisions for the next five years. The law is governed both by EU legislation that introduces common rules for member states, and by detailed differing national laws. For this reason, the elections in question are implemented in accordance with the rules set forth in the treaty regulations and the electoral laws of each country. This article discusses in detail the issues related to, among other things, electoral rights, the procedure and organization of EP elections, the voting system used, and presents the issues of turnout in individual electoral districts in relation to the EP elections held in Poland 2019.